Balanced nutrition and crop production practices for the study of grain sorghum nutrient partitioning and closing yield gaps - McHenry, Bailey Marie (Kansas State University, 2016)
Mid-west grain sorghum (Sorghum bicolor (L.) Moench) producers are currently obtaining much lower than attainable yields across varying environments, therefore, closing yield gaps will be important. Yield gaps are the difference between maximum economic attainable yield and current on-farm yields. Maximum economic yield can be achieved through the optimization of utilizing the best genotypes and management practices for the specific site-environment (soil-weather) combination. This research project examines several management factors in order to quantify complex farming interactions for maximizing sorghum yields and studying nutrient partitioning. The factors that were tested include narrow row-spacing (37.5 cm) vs. standard wide row-spacing (76 cm), high (197,600 seeds haˉ¹) and low (98,800 seeds haˉ¹) seeding rates, balanced nutrient management practices including applications of NPKS and micronutrients (Fe and Zn), crop protection with fungicide and insecticide, the use of a plant growth regulator, and the use of precision Ag technology (GreenSeeker for N application). This project was implemented at four sites in Kansas during 2014 (Rossville, Scandia, Ottawa, and Hutchinson) and 2015 (Topeka, Scandia, Ottawa, Ashland Bottoms) growing seasons. Results from both years indicate that irrigation helped to minimize yield variability and boost yield potential across all treatments, though other factors affected the final yield. In 2014, the greatest significant yield difference under irrigation in Rossville, KS (1.32 Mg haˉ¹) was documented between the ‘low-input’ versus the ‘high-input’ treatments. The treatment difference in grain sorghum yields in 2014 was not statistically significant. In 2014, the Ottawa site experienced drought-stress during reproductive stages of plant development, which resulted in low yields and was not influenced by the cropping system approach. In 2015 the treatments were significant, and in Ottawa, narrow row spacing at a lower seeding rate maximized yield for this generally low-yielding environment (<6 Mg haˉ¹) (treatment two at 6.26 vs. treatment ten at 4.89 Mg haˉ¹). Across several sites, including Rossville, Hutchinson, Scandia, Topeka, and Ashland, a similar trend of narrow row spacing promoting greater yields has been documented. Additionally, when water was not limiting sorghum yields (i.e., under irrigation), a balanced nutrient application and optimization of production practices did increase grain sorghum yields (‘high-input’ vs. ‘low-input’; the greatest difference was seen in 2014 in Rossville, 1.2 Mg haˉ¹, and in 2015 in Ashland, 1.98 Mg haˉ¹). In the evaluation of nutrient uptake and partitioning in different plant fractions, there was variability across all site-years which did not always follow the same patterns as the yield, however, the low-input treatment was shown to have significantly lower nutrient uptakes across all the nutrients evaluated (N, P, K, S, Fe, Zn) and across most fractions and sampling times. The objectives of this project were to identify management factors that contributed to high sorghum yields in diverse environments, and to investigate nutrient uptake and partitioning under different environments and crop production practices.
Keywords: Management practicesGrain sorghum; Nutrient uptake; Yields